2010
DOI: 10.1007/s00203-010-0599-z
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and genetic factors that contribute to Escherichia coli K-12 biofilm formation

Abstract: Biofilms are communities of bacteria whose formation on surfaces requires a large portion of the bacteria's transcriptional network. To identify environmental conditions and transcriptional regulators that contribute to sensing these conditions, we used a high-throughput approach to monitor biofilm biomass produced by an isogenic set of Escherichia coli K-12 strains grown under combinations of environmental conditions. Of the environmental combinationsd, growth in tryptic soy broth at 37°C supported the most b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
35
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 51 publications
6
35
0
Order By: Relevance
“…Several previous studies from our lab demonstrate that the absence of motility enhances the ability of E. coli to form substantial amounts of biofilm. As one example, strains transformed with the FlhD expressing plasmid pXL27 showed diminished biofilm forming capabilities (Prüß et al, 2010). Additionally, ongoing studies carried out in the lab with E. coli O157:H7 and the E. coli K-12 strains MC1000 and AJW678 point in the same direction, exemplifying our belief that FlhD and motility are detrimental to biofilm formation for our bacterial strains and under the conditions of our experiments (Sule et al, unpublished data).…”
Section: Biological Analysis Of the Datasupporting
confidence: 69%
See 1 more Smart Citation
“…Several previous studies from our lab demonstrate that the absence of motility enhances the ability of E. coli to form substantial amounts of biofilm. As one example, strains transformed with the FlhD expressing plasmid pXL27 showed diminished biofilm forming capabilities (Prüß et al, 2010). Additionally, ongoing studies carried out in the lab with E. coli O157:H7 and the E. coli K-12 strains MC1000 and AJW678 point in the same direction, exemplifying our belief that FlhD and motility are detrimental to biofilm formation for our bacterial strains and under the conditions of our experiments (Sule et al, unpublished data).…”
Section: Biological Analysis Of the Datasupporting
confidence: 69%
“…Although the carbon sources that promoted the highest biofilm amounts were different for the two strains, they still were in the same pathway. The previous high-throughput experiment that had pointed towards nutriition as instrumental in determining biofilm associated biomass had also postulated acetate metabolism as one of the key players in biofilm formation (Prüß et al, 2010). Phosphorylation of OmpR and RcsB by the activated acetate intermediate acetyl phosphate (Kenney et al, 1995) and acetylation of RcsB by acetyl-CoA (Thao et al, 2010) have been described in the past.…”
Section: Biological Analysis Of the Datamentioning
confidence: 99%
“…For instance, specific environmental factors may provide suitable carbon and energy sources or metabolic products, thus serving as indicators of favorable conditions for growth. Prüß et al screened E. coli K-12 wild type and mutants cultured in 96-well polystyrene plates for the effect of multiple combinations of environmental conditions and carbon sources on biofilm formation (131). The phenotype microarray experiments illustrated that carbon sources that are metabolized to acetyl coenzyme A, acetyl phosphate, and acetate are particularly supportive of biofilm formation.…”
Section: Why Attach In the First Place?mentioning
confidence: 99%
“…Moreover, strains inactivated in genes associated with acetate metabolism demonstrated reduced biofilm formation. The findings suggested that acetate metabolism functions as a metabolic sensor, transmitting changes in environmental conditions to mechanisms regulating biofilm biomass and structure (131). Other nutritional cues have been shown to serve as building blocks of adhesins and polysaccharides that are directly perceived as signals that activate particular regulatory cascades.…”
Section: Why Attach In the First Place?mentioning
confidence: 99%
“…Moreover, the importance of AcP in processes that are critical for bacterial virulence and persistence has been demonstrated in certain eubacteria, including Escherichia coli (11,12,14), Staphylococcus aureus (15), Streptococcus pneumoniae (16), Listeria monocytogenes (17), and Clostridium acetobutylicum (18, 19), although not in S. mutans or other oral pathogens. Some effects of AcP on the properties of bacteria related to virulence include the finding that inactivation of the Pta-Ack pathway results in biofilm formation that is quantitatively and architecturally distinct from that in the parental strains (14,16,20). In E. coli, analysis of the transcriptome showed that the expression of about 100 genes is responsive to intracellular AcP levels, many of which encode products involved in bacterial motility or adherence (14).…”
mentioning
confidence: 99%